2023
DOI: 10.3390/medicina59020192
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salvage Surgery in Persistent Cervical Cancer after Definitive Radiochemotherapy: A Systematic Review

Abstract: Background and Objectives: The standard treatment approach in locally advanced cervical cancer (LACC) is exclusive concurrent chemoradiation therapy (RTCT). The risk of local residual disease after six months from RTCT is about 20–30%. It is directly related to relapse risk and poor survival, such as in patients with recurrent cervical cancer. This systematic review aims to describe studies investigating salvage surgery’s role in persistent/recurrent disease in LACC patients who underwent definitive RTCT. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The recurrence rate after salvage surgery in our study is based on small numbers and is comparable with the reported literature. Two previously published systematic reviews reported overall relapse rates of 32% and 31% after salvage surgery [ 10 , 28 ]. In addition to the recurrence rate, Sardain et al reported that salvage exenteration for recurrent disease increased the five-year OS from 20% to 64% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recurrence rate after salvage surgery in our study is based on small numbers and is comparable with the reported literature. Two previously published systematic reviews reported overall relapse rates of 32% and 31% after salvage surgery [ 10 , 28 ]. In addition to the recurrence rate, Sardain et al reported that salvage exenteration for recurrent disease increased the five-year OS from 20% to 64% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients have an unfavorable prognosis, with a reported 5-year survival rate of less than 5% [ 9 ]. Patients treated with CRT are clinically and/or radiologically examined during the follow-up period to evaluate the response rate of CRT [ 10 ]. Detection of locoregional residual disease can be challenging due to the effects of radiotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations for stage IA2 patients, and stage IB1, IB2 and selected IIB3-IIA1 patients who do not desire fertility preservation, are type B radical hysterectomy (RH) and type C RH, respectively ( 1 , 2 ). For patients with advanced disease, it is still inconclusive whether salvage hysterectomy either extrafascial or radical is effective in persistent or recurrent disease after definitive chemoradiation therapy ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The persistent global disease burden of CC underscores the crucial need for early detection and tertiary prevention, especially in resource-limited settings. A recent report showed that pelvic lymph node (PLN) involvement reduced the 5-year survival rate for CC from 91.2% to 59.8% (5), significantly affecting the prognosis and shifting treatment from surgery to chemoradiation or brachytherapy (6)(7)(8). Guidelines recommend radiological imaging (computed tomography [CT], magnetic resonance imaging [MRI], and positron emission tomography [PET]/CT) for CC at stage IB2 or greater, particularly for nodal or extrapelvic tumor evaluation (7).…”
Section: Introductionmentioning
confidence: 99%